PROBLEM BASED LEARNING SEBAGAI SUATU STRATEGI PEMBELAJARAN UNTUK MENUMBUH-KEMBANGKAN ATMOSFER KEBEBASAN INTELEKTUAL - Sutrisno, Sutrisno (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abstract: Problem based learning (PBL) is a pedagogical approach which involve and use the scenarios or complex situations to assist students in problem solving, commensurate or consistent with the character of collaborative learning. During the collaboratve study project, students work in a small group to write a scientific work, constructing a model, or generate awide range of products- all of them rrequire a problem solving skills. Teachers with all the facilities and means role as learning facilitator. PBL as a pedagogical approach is essentially characterized by (1) learning is based on the need to solve problems (2) the study take place independently and collaborativly with facilitators,(3) solutions of the problems based on the inquiry or investigation activity, (4) learn to develop creativity and self-assessment and (5) there is a direct product or the students real work shortly after the pedagogy. The learning outcome of PBL approach includes cognitive, affective, and psychomotor, but more emphasis on self-development in the learning process.Key words: problem based learning, collaborative learning, assessment and self evaluation